10q=7-3q

Simple and best practice solution for 10q=7-3q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10q=7-3q equation:



10q=7-3q
We move all terms to the left:
10q-(7-3q)=0
We add all the numbers together, and all the variables
10q-(-3q+7)=0
We get rid of parentheses
10q+3q-7=0
We add all the numbers together, and all the variables
13q-7=0
We move all terms containing q to the left, all other terms to the right
13q=7
q=7/13
q=7/13

See similar equations:

| -2x–13=-3x–5 | | 25x+30=65x+20) | | 13=y/6.25+8 | | 3x-6/3+9=14 | | 60=6x+30 | | 8b+88=144 | | 5x-4+1x=20 | | 7x-63=133 | | 2n-5n=-15 | | -5/9x-2/45x+1/5x=-54 | | 9x-21=3x-15 | | 6(4r+1)-6(-8r-6)=-30 | | 9n+36=57 | | 1/2(3+9)=h | | 4x-12=3x=18=20 | | A=1/2(3+9)h | | −9x+27=108 | | 9.38=3.5+1.2(6.3–7x) | | 3x-3=26 | | 68.88=1.99-45x | | y–417=13 | | =3q+2 | | 10x-(6x-5)=13 | | 5(3r-2)=2(5r+2) | | y–4+17=13 | | 7x-12-4x=15 | | y–4+ 17=13 | | –2(t–8)=8 | | 10y-8=11y-9 | | x-2+3=-2=-3 | | 4a+24=92 | | Y+(x+23)=180 |

Equations solver categories